Planering i samhällen med konjunkturkänslig industri : Riktlinjer för Svappavaara - Olsson, Therese (2014)
Small societies characterized by a dominating industry depend on the job opportunities from the industry. Since the job opportunities vary with the economical fluctuations, the structure and demand of the society varies as well.A set of guidelines have been developed to create a more solid structure of the society despite the cyclical fluctuations and to reduce the impact of the industry. These include the importance of different line of businesses to prevent the impact of the industry. It clarifies that the identity and attractiveness of the society are very important, as it can encourage commuting instead of inhabitants moving when work varies. Good communications such as roads and railways are essential for commuting and hence to regional expansion. To have a more choices where to work IT-solutions are very important.Meeting points and different kinds of targets, connected to each other promotes movement and attractiveness. Targets such as shops and restaurants, activity places for children and youths as well as schools. Flexible solutions such as availability to change the use of areas in the society, and to provide the opportunity to expand different functions of the society are important. Temporary housing which easily can be set up or dismantled are required to prevent buildings without use. Housing demand for the elderly should be reviewed and made possible in connection with the center of the community. The capacity of the technical systems should be reviewed. Stormwater management is important to clean the emissions from the industry and waste energy from the industry should, if possible, be used for district heating. In all measures, it is important to take into account the existing society and its structure to try to create a social robustness.The general guidelines for planning in cyclical societies were adapted to the mine society Svappavaara in the municipality of Kiruna, Sweden. The proposal was developed from the guidelines and conditions and qualities of Svappavaara is intended to partly been ...